(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
Mentha spicata and M. cardiaca introduced in Bangladesh were studied for their essential oil content and compositions of the oil. The essential oil from M. spicata contains carvone (73.29 %), d-limonene (7.59 %) and dihydrocarvone (3.83 %) as major constituents out of the 21 components. The essential oil from M. cardiaca contains carvone (60.9 %) and limonene (21.58 %) as major constituents out of the 35 components. Bangladesh J. Sci. Ind. Res. 42(1), 79-82, 2007